Pengaruh Pendidikan Agama Islam dalam Keluarga terhadap Karakter Remaja di Desa Bukit Sari Kabupaten Bungo - Tryanto, Rudi; Afrinaldi, Afrinaldi; Wati, Salmi; M, Iswantir (Al-DYAS, 2023)
The background of this research is that there are still teenagers who violate the rules in society and commit delinquency in the community, such as there are still teenagers who do not respect and respect people, and the authors see that there are still teenagers who are not polite in speaking and lack respect for elders. This study uses a quantitative correlation approach. The data analysis technique that the author did was a prerequisite analysis test in the form of a data normality test and a linearity test. Then the final data analysis the author uses is correlation analysis. Based on the results of the study it can be understood that there is an influence between Islamic religious education in the family and the character of adolescents. The strength of the relationship between aspects of parental guidance and adolescent character is shown by looking at Sig. between the two variables is 0.000 (correlated). The person correlation value of Islamic Religious Education in the Family is +0.816 and the person correlation value for Adolescent Character is +0.816. (the positive sign in front of the personal correlation indicates that the form of the relationship between the two variables is a positive form of relationship). So, it can be concluded that "There is an influence of Islamic religious education in the family on the character of adolescents in Bukit Sari, Bungo Regency" and in conclusion the hypothesis H0 is rejected, and H1 is accepted. This is due to = 0.816 which is in the coefficient interval of 0.800-0.100 so that the level of correlation between the two variables is included in the very strong category.